Optimization and spray-drying of nisin-enriched fermentation broth for antimicrobial powder production - Polat, Asli; Demirgul, Furkan; Simsek, Omer (TAYLOR & FRANCIS INC, 2025)
Growing consumer demand for natural preservatives has increased interest in bacteriocins such as nisin for food preservation, yet the high cost of downstream processing and purification limits widespread use. This study developed a cost-effective antimicrobial powder by producing nisin directly from fermentation broth without prior purification. Nisin production by Lactococcus lactis subsp. lactis N8 was optimized using Response Surface Methodology (RSM) based on a face-centered Central Composite Design, using demineralized whey (DW), soybean meal (SM), and glucose syrup (GS) as substrates. The regression model explained most variation in antimicrobial activity (R2 = 0.98, adj-R2 = 0.97, pred-R2 = 0.87) and identified the optimum. Maximum activity against Micrococcus luteus NCIMB 86100 reached 9,120 IU/mL at 100 g/L DW, 50 g/L SM, and 50 g/L GS. Spray-drying with different maltodextrin and DW levels was then tested to maximize nisin adsorption. The most effective formulation, using 5% maltodextrin, yielded an antimicrobial powder with an activity of 41,000.50 IU/g, representing approximately a 4.5-fold enhancement compared to the optimized fermentation broth. These results show that active nisin can be incorporated into antimicrobial powders through direct fermentation and spray-drying, offering a scalable, economical clean-label approach for food preservation.
Keywords: Antimicrobial powder; bacteriocin; food safety; Lactococcus lactis; nisin; PHYSICOCHEMICAL PROPERTIES; LISTERIA-MONOCYTOGENES; BACTERIOCIN PRODUCTION; GROWTH; COMBINATION; STABILITY; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology